Efficacy of Online Intervention for ADHD: A Meta-Analysis and Systematic Review - Shou, Songting; Xiu, Shengyao; Li, Yuanliang; Zhang, Ning; Yu, Jinglong; Ding, Jie; Wang, Junhong (Frontiers in Psychology, 2022)
Background: With the popularity of computers, Internet and the global spread of COVID-19, more and more attention deficit hyperactivity disorder (ADHD) patients need timely intervention through the Internet. At present, there are many online therapy schemes that may help these patients. It is necessary to integrate data to analyze their effectiveness. Objectives: Our purpose is to integrate the ADHD online therapy trials, study its treatment effect and analyze its feasibility, and provide reference information for doctors in other institutions to formulate better treatment plans Methods: From the beginning to December 1, 2021, we conducted a search on PubMed, EMBASE and Cochrane library to test the ADHD of online therapy. We used the Cochrane bias risk tool to assess the quality of included studies, used the standardized mean difference (SMD) as an effect scale indicator to measure data. Random effects model, subgroup analysis were used to analyze the data. Results: 6 randomized controlled trials (RCTs) were identified, including 256 patients with ADHD. These studies showed that online therapy was more effective than waiting list in improving attention deficit and social function of adults and juveniles with ADHD. The sample size of the test group was 123, the sample size of the control group was 133, and the combined SMD was -0.73 (95% confidence interval: - 1.01, - 0.44). The social function scores of subjects were calculated in 6 studies. The sample size of the experimental group was 123 and the control group was 133. The combined SMD was -0.59 (95% confidence interval: - 0.85, - 0.33). Conclusions: The results show that online therapy of ADHD may be an effective, convenient and widely used treatment method. In the future, we need more online therapy research to improve the symptoms of different patients, especially for some patients who have difficulty accepting face-to-face treatment.